2014
DOI: 10.1021/jo502288q
|View full text |Cite
|
Sign up to set email alerts
|

Photoredox Catalysis in a Complex Pharmaceutical Setting: Toward the Preparation of JAK2 Inhibitor LY2784544

Abstract: We report a detailed investigation into the application of visible light-mediated photocatalysis to a challenging bond construction in a complex pharmaceutical target. The optimized reaction allowed the direct coupling of N-methylmorpholine with an unfunctionalized pyridazine in good yield and selectivity, and with high purity of the product isolated via crystallization. The reaction also facilitated the expedient synthesis of a range of analogues via the use of other commercially available N-methyl substitute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
54
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 59 publications
1
54
0
3
Order By: Relevance
“…In a collaboration with Eli Lilly, Stephenson demonstrated that photoredox-mediated coupling of N -methylmorpholine with pyridazine 92 provides rapid access to an intermediate in the synthesis of JAK2 inhibitor LY2784544 (Scheme 34a). 163 Here, a range of analogues could be readily synthesized by simply employing different tertiary amine coupling partners. In addition, recent advances from our group in the field of metallaphotoredox has enabled the rapid construction of medicinally relevant compounds such as fenofibrate 118 and edivoxetine·HCl 121 (Scheme 34b).…”
Section: Applications Of Photoredox Catalysismentioning
confidence: 99%
“…In a collaboration with Eli Lilly, Stephenson demonstrated that photoredox-mediated coupling of N -methylmorpholine with pyridazine 92 provides rapid access to an intermediate in the synthesis of JAK2 inhibitor LY2784544 (Scheme 34a). 163 Here, a range of analogues could be readily synthesized by simply employing different tertiary amine coupling partners. In addition, recent advances from our group in the field of metallaphotoredox has enabled the rapid construction of medicinally relevant compounds such as fenofibrate 118 and edivoxetine·HCl 121 (Scheme 34b).…”
Section: Applications Of Photoredox Catalysismentioning
confidence: 99%
“…[83][84][85][86][87][88] N,N-Dimethylanilines undergo addition onto electron-deficient alkenes 9 via α-amino radical intermediates and cyclization to give quinoline derivatives 10 (Scheme 31). MacMillian utilized nucleophilic α-amino radicals generated using visible light photoredox Ir(III) catalysis in substitutions onto electron-deficient dicyanobenzenes and heterocyclic variants, where the reductive loss of cyanide occurs (Scheme 33).…”
mentioning
confidence: 99%
“…In the current context, efforts were thus directed toward the generation of α-amino radicals starting from chiral N -trifluoroboratomethyl salts. These versatile α-amino radicals [6,2735] were envisioned to allow the assembly of enantioenriched building blocks of potential value. [6,28] …”
mentioning
confidence: 99%
“…The intermediacy of α-amino radicals to elaborate aryl- and heteroaryl substructures has recently been demonstrated in photoredox catalysis [6,25,28,36] from both unfunctionalized amines (toward the preparation of JAK2 inhibitor LY2784544), [6] and those with the TMS [35,37,38] and CO 2 H [2,39] activating groups (Scheme 1). …”
mentioning
confidence: 99%